A GEOARCHAEOLOGICAL INVESTIGATION OF THE STREET OF THE DEAD AT THE TLAJINGA DISTRICT, TEOTIHUACAN, MEXICO. Issue 1 (11th April 2019) - Stahlschmidt, Mareike C.; McClung de Tapia, Emily; Gutiérrez-Castorena, Ma. del Carmen
Abstract: Archaeological investigations undertaken by the Proyecto Arqueológico Tlajinga Teotihuacán are focused on understanding urban expansion and household economies in this southern district of the city. Our geoarchaeological research addresses similar topics through examination of relevant microstratigraphic and botanical signatures as well as those relevant to reconstructing paleoenvironment. We investigated four different contexts at Tlajinga: the southern extension of the Street of the Dead, an obsidian working area outside Compound 17:S3E1, anthropogenic and natural layers below Compound 18:S3E1, and a soil profile at the San Lorenzo river. We employed micromorphological, pollen, and phytolith analyses as well as standard soil analytics to study the various deposits in these contexts. Our analysis demonstrates artificial lowering of the tepetate for continuing the axis of the Street of the Dead, microdebitage from obsidian working outside Compound 17:S3E1, and the preservation of in situ burning activities at Compound 18:S3E1. Further, we reconstruct alluvial infilling of the Street of the Dead with pedogenetic overprinting and present further evidence on the occurrence and variability of the Black San Pablo Paleosol and its agricultural significance.